The Value, Obstacle and Strategy of Digital Empowerment Physical Education in Primary School - Yuan, Wei; Samsudin, Shamsulariffin; Abdullah, Borhannudin; Farizan, Noor Hamzani; Hassan, Muhammad Zarif; Cheng, Ji (Journal of Ecohumanism, 2024)
With the title of "The Value, obstacle and Strategy of physical education teaching in primary school with digital empowerment", this paper discusses the value, obstacle and optimization strategy from three angles. Through the research, it is found that digital technology can bring great value in primary school physical education, including the advantages of improving teaching effect, enhancing student participation, personalized learning and all-round development. However, digital physical education also faces some obstacles, such as the problem of capital investment, the lack of teachers' digital literacy and professional ability, and the unequal investment in educational resources. In order to optimize the digital effect of primary school physical education, six optimization strategies are proposed: increasing funding investment and sponsorship, enhancing teachers' digital literacy and professional ability, optimizing the investment and distribution of educational resources, promoting students' and parents' participation and recognition, formulating privacy and security policies, and establishing a digital primary school physical education evaluation system in the digital era. Through the implementation of these strategies, the digital development of primary school physical education can be further promoted and the teaching quality and students' comprehensive literacy can be improved.